Experimental equilibria of several β/βo–Ti–Al–Nb alloys containing ωo phase. (27th November 2019) - Yang, L F; Xu, Y; Xu, R F; Yu, M J; Zhang, D M; Yuan, N Q; Lin, J P
Abstract: The phase equilibria of several (6, 8, 10) at% Nb–TiAl alloys are experimentally determined by the morphologic, crystallographic and thermal analysis methods. The thermodynamically determined phase equilibria reveal that ω o phase transforms from α 2 phase, having no β / β o phase retained at ambient temperature. While, the β / β o phase are experimentally observed in the samples annealed at 1400 °C followed by a slow cooling rate (∼10 °C min −1 ). Furthermore, the transformation of β o  ↔  ω o, as well as the disorder-order transition of β  ↔  β o, is unambiguously detected, within the certain transformation temperatures.